Where We Dwell in Common - Haight, Roger (Horizons, 2005)
The great surge of Christian missionary activity during the course of the nineteenth century elicited a new concern for church unity. Was this missionary activity, after all, spreading division? In 1910 representatives of Protestant churches came together to respond to that question in Edinburgh at The World Missionary Conference. The conference in its turn channeled the concern to the sending churches. Although somewhat slowed down by World War I, the ecumenical movement grew and was punctuated by landmark events in The Universal Christian Conference on Life and Work (Stockholm, 1925) and The World Conference of Faith and Order (Lausanne, 1927). The report of this second conference included a description of what the churches assembled in their representatives shared in common and the many things that distinguished and sometimes divided them. When the World Council of Churches came into existence in August of 1948, the Faith and Order movement was integrated into it as a distinct agency whose concern was the doctrinal unity of the churches. Its signal achievement thus far has been the document entitled Baptism, Eucharist, and Ministry, frequently referred to as the Lima document, which sketches a proposal for a common understanding of these three aspects of the church across the churches. This document is the best example of what I will call "transdenominational ecclesiology," and the fact that it has received so much attention from the churches indicates that it plays some important role in the whole church.